Pseudokinases-remnants of evolution or key allosteric regulators? - Zeqiraj, Elton (Elsevier Science, 2010)
Protein kinases provide a platform for the integration of signal transduction networks. A key feature of transmitting these cellular signals is the ability of protein kinases to activate one another by phosphorylation. A number of kinases are predicted by sequence homology to be incapable of phosphoryl group transfer due to degradation of their catalytic motifs. These are termed pseudokinases and because of the assumed lack of phosphoryltransfer activity their biological role in cellular transduction has been mysterious. Recent structure–function studies have uncovered the molecular determinants for protein kinase inactivity and have shed light to the biological functions and evolution of this enigmatic subset of the human kinome. Pseudokinases act as signal transducers by bringing together components of signalling networks, as well as allosteric activators of active protein kinases.